Exploration of climate mediated decline in a critically endangered southern hemisphere conifer over the last 40 years / Annabelle J. Rogers - Rogers, Annabelle J (Department of Biological Sciences, 2015)
Widdringtonia cedarbergensis is a critically endangered conifer restricted entirely to the Cederberg Mountain range in the Western Cape of South Africa. This study aimed to assess whether contemporary climate change could be a driver in the recently documented tenfold decline of W. cedarbergensis in the last 40 years. By building distribution models using Maxent bioclimatic modelling for pre- and post- 1970’s point occurrence data, the distribution of the species pre- and post-1970’s were compared and assessed for significant change. Models predicted a clear range contraction in W. cedarbergensis from pre- to post- 1970. The present model predictions of suitability occur in a tight altitudinal band on the mid to upper slopes of the middle Cederberg (minimum of 1048m to a maximum of 1530m). However, the climatic predictions associate the present model distribution with relatively warmer and drier areas compared to that of the pre- 1970 model, suggesting a shift down slope rather than upslope. This is possibly due to the exaggeration of the upper limit of distribution for the pre-1970’s model that predicts W. cedarbergensis to occur as high as 1850m. This is unlikely due to the high prevalence of frost at this elevation. Though any climatic signal was complicated due to historical data error, high confidence in the present model prediction adds a valuable contribution to a body of literature that documents the decline of W. cedarbergensis and has important implications for conservation management of the species.